Factors influencing pre‐ovulatory follicle diameter and weaning‐to‐ovulation interval in spontaneously ovulating sows in tropical environment. Issue 12 (3rd November 2020) - Pearodwong, Pachara; Tretipskul, Chanyuth; Panyathong, Raphee; Tummaruk, Padet
Abstract: Follicle development and timing of ovulation are indicators of the reproductive performance of sows. The present study aimed to determine factors influencing pre‐ovulatory follicle diameter and weaning‐to‐ovulation interval (WOI) in spontaneously ovulating sows in tropical climates with special emphasis on breed, parity and backfat thickness at weaning. In total, 80 sows were included in the study. Follicle development was determined by using transrectal real‐time B‐mode ultrasonography every 6 hr after standing oestrus. Weaning‐to‐oestrous interval (WEI), oestrous‐to‐ovulation interval (EOI), WOI and the diameter of graafian follicles were investigated in relation to breed, parity number (1, 2–3 and 4–7) and backfat thickness (low, moderate and high) of sows. Overall, WEI, EOI, WOI and the pre‐ovulatory follicle diameter were 92.5 ± 21.6 hr, 64.3 ± 19.3 hr, 156.3 ± 29.1 hr and 10.3 ± 2.0 mm, respectively. Pre‐ovulatory follicle size was smaller in primiparous sows compared with sows of greater parity, 4–7 (9.7 ± 0.51 and 11.7 ± 0.52 mm, respectively, p < .05). Weaning‐to‐ovulation interval was positively correlated with WEI ( r = 0.75, p < .001) and EOI ( r = 0.66, p < .001), but negatively correlated with size of the graafian follicle ( r = –0.34, p < .01). Sows with a shorter WEI had a larger pre‐ovulatory follicle diameter (at 64 hr after oestrus) ( r = –0.37, p < .01). Sows with low backfat thickness had a WOI 23.4 hr longer than those with moderate backfat thickness ( p < .05) and 17.6 hr longer than sows with a high backfat thickness ( p = .140). The follicle diameter in primiparous sows with high backfat thickness (11.7 ± 1.1 mm) was higher than in those with low (8.9 ± 0.7 mm, p < .05) or moderate (8.6 ± 0.8, p < .05) backfat thickness. In conclusion, factors influencing follicle diameter and WOI in sows included parity number and backfat thickness at weaning. The impact of backfat thickness on follicle diameter, WEI and WOI was most pronounced in primiparous sows.